Obtaining and Analysis of Optical Absorption Spectrum of Fisher Rat Blood with Hepatic Damage by Photoacoustic Spectroscopy - Alvarado Noguez, M. L.; Cano Europa, E.; Franco Colín, M.; Hernández Aguilar, C.; Domínguez Pacheco, F. A.; Cruz Orea, A. (Revista Mexicana de Ingenieria Biomedica, 2017)
Photoacoustic Spectroscopy (PAS) stand outs among Photothermal techniques due to its versatility for the characterization of different types of materials, including biological samples. In this study, were compared and analyzed by PAS, the differences between the optical absorption spectra of blood of male Fisher rats, in three cases, control (healthy rats), liver damage and liver damage treated with Curcuma longa. The experimental results show differences in the optical absorption spectra of each analysed case, therefore PAS would be proposed as a non conventional complementary technique, to study the effect of Curcuma longa in induced liver damage for an animal model.